LEOPARD Syndrome with a Sporadic PTPN11 Mutation in a Saudi Patient - Hussein M. Alshamrani; Luai M. Assaedi; Jumanah A. Bahattab; Abdulrahman M. Mohammad; Magdy R. Abdulghani (Case Reports in Dermatological Medicine)
LEOPARD syndrome (LS) is a rare autosomal dominant inherited or sporadic genetic disorder caused commonly by missense mutations in the protein-tyrosine phosphatase-nonreceptor type 11 (PTPN11) gene. Due to its rarity and a high chance of misdiagnosis, the epidemiological profile of LS is poorly established. To the best of our knowledge, this is the second report with a documented PTPN11 gene mutation in Saudi Arabia.